FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN (STUDI DI PATRA JASA CONVENTION CENTER SEMARANG) - Heri Prabowo (BBM (Buletin Bisnis & Manajemen), 2016)
This research analyzes many factors which influence of the employees working. The pupose of the research is fainding many factors which influence the employee working. The contents is wisdom compentation distribution and satisfied of working releated with the influence the employee working. The object of this research is employees of Patra Jasa Convention Centre.Purposive sampling which choisen is to find out the data which needed in this studies there are 40 responden and all of the are Patra Jasa Convention Centre employee. The data analysis used SPSS program 19 series. Before doing regreesion analysis, the process analysis is trought many steps whisvh one of the is validity analysis, reliability test and classic assumtion test.In this research has three hypothesis and depards of the research analysis show that three hypothesis are acepted, it means the conclution of this research wisdom compentation distribution it influence satisfied of working towards increasing of employees working.Kata Kunci : wisdom distribution compentation, satisfied of working and employees working